Rancang Bangun Sistem Pengontrol Irigasi Otomatis Menggunakan Mikrokontroller Arduino Uno - Nurul Fauziah; Akhlis Munazilin; Firman Santoso (Universitas Islam Raden Rahmat, Malang, 2024)
Current advances in science and development make regular daily existence progressively simpler. Where science and advancement are by and large applied with machines or equipment, human work should be done truly, and time abbreviated. Modified water framework control is a motorization methodology that uses an Arduino microcontroller. This examination utilizes abstract investigation and model improvement strategies. The reason for using this system is to create or foster specific things. This procedure is applied to investigate strategies into 6 phases, to be specific (1) needs, (2) fast arrangement, (3) structure model, (4) client evaluation, (5) refinement model, and (6) execution. This framework utilizes an ultrasonic sensor type HC-SR04 which is utilized to measure the distance of water from an article.